2008
DOI: 10.1177/0269216308090770
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a three-day communication skills course in changing nurses’ communication skills with cancer/palliative care patients: a randomised controlled trial

Abstract: This multi-centre, two-armed parallel-group pragmatic randomised controlled trial (RCT) evaluated the effectiveness of a 3-day communication skills course in changing nurses' communication skills. The primary outcome was the change in the nurses' communication skills score from pre-course to 12 weeks post-course. The main secondary outcome was the change in the nurses' level of confidence in communicating with patients. A total of 172 nurses were randomised to the course or control. The communication skills sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 19 publications
0
98
0
4
Order By: Relevance
“…Previous work has shown that intensive communication skills training can change the communication behaviors and increase the confidence of clinic-based cancer palliative care nurses. 54 Given this evidence on communication improvement, the present study provides clinical examples on which to base future communication skills training to advance hospice clinicians' interactions with patients and families.…”
Section: Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous work has shown that intensive communication skills training can change the communication behaviors and increase the confidence of clinic-based cancer palliative care nurses. 54 Given this evidence on communication improvement, the present study provides clinical examples on which to base future communication skills training to advance hospice clinicians' interactions with patients and families.…”
Section: Limitationsmentioning
confidence: 96%
“…There is a widely held assumption that nurses are innately skilled communicators given their reputation for empathy and their need to interface with other healthcare providers, patients and families. 1 However, nursing curricula, including that in hospice and palliative nursing, are largely geared toward direct physical care and may not adequately provide nurses with the unique communication skills required.…”
Section: Introductionmentioning
confidence: 99%
“…Although Williams et al 22 showed improved overall performance of EOL conversations with standardized patients after an intensive workshop, several other interventions have not significantly improved overall performance despite similar amounts of teaching time. 12,13 The use of ''multiple day'' training programs (ranging from 24 to 105 hours) [23][24][25][26] or ''booster'' sessions 27,28 have been used successfully to improve the communication skills of more experienced clinicians. Although PGY-1 residents require these skills, this much time commitment would be challenging in light of new duty hour requirements imposed by the Accreditation Council of Graduate Medical Education in July 2011.…”
Section: Szmuilowicz Et Almentioning
confidence: 99%
“…It has been demonstrated that effective communication usually reduces stress, anxiety, and uncertainty in patients (1) and simultaneously influences the rate of patients' recovery, ability to comply with treatments, and psychosocial adjustment (2,3). In addition to this, it was found that effective communication affects distress levels of health care specialists (4).…”
Section: Introductionmentioning
confidence: 99%